Rodent faunas, their paleogeographic pattern, and responses to climate changes from the early Eocene to the early Oligocene in Asia - Li, Qian; Li, Qi; Xu, Rancheng; Wang, Yuanqing (Frontiers in Ecology and Evolution, 2022)
Rodents are an important component in Paleogene terrestrial ecosystems. Their evolution and faunal turnover are considered to have been influenced and triggered by global climate change. Here we compiled the rodent faunas from early Eocene to early Oligocene in Asia to discuss the rodent faunal turnover and its correlation with the paleogeographic and paleoclimate changes. Successive rodent faunas from early Eocene to early Oligocene are recorded in East Asia, the rodent faunal turnover are obviously affected by the paleoclimatic changes. During the Ulangochuian (after the MECO) when temperatures declined slowly, the rodent fauna showed a clear decline in the generic diversity and a transformation from ctenodactyloid dominant to cricetid-dipodid dominant. During the Eocene-Oligocene transition (EOT) and the global cooling, the rodent fauna exhibited considerable high generic diversity of cricetid, dipodid and ctenodactylid. The low temperatures during the Ulangochuian and the Ergilian in East Asia served as a habituation ground for the cricetids and dipodids, which became preadapted for the EOT, successfully helping the rodent as the dominant faunas after EOT. The rodent faunas from south Asia formed a relatively isolated group in much of the Eocene and early Oligocene, sometimes they were closer to European or African than to Asian rodents, the striking differences between the rodent faunas from South Asia and East Asia are the results of great difference in habitats.